Increasing Awareness of Tax Obligations for MSME Actors - Roekhudin; Devy Pusposari; Lilik Purwanti; Soelchan Arief Effendi; Diana Nurindrasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to provide education and assistance to Micro, Small and Medium Enterprises (MSMEs) by providing an understanding of the basic concepts of taxation, tax rights, and obligations for MSMEs. The method of implementing community service activities is carried out in several stages. The first stage is the planning stage through observation and preliminary interviews on the subject of community service. The second stage is the implementation of activities in the form of training, which is carried out through the presentation of materials, calculation practice, reporting, and tax payment procedures, as well as discussions. The third stage is monitoring, which aims to address the problems faced by MSMEs in fulfilling their tax obligations independently. MSME owners need to be equipped with adequate tax knowledge to increase their awareness of MSME tax compliance. Moreover, limited knowledge is one of the obstacles to the development of MSMEs. Through continuous participation in tax socialization activities such as tax advice and seminars, MSME taxpayers using e-commerce will increase their awareness and compliance. Based on the activities carried out, MSME owners (actors) in Pare Kediri as MSME business operations managers gain a significant understanding of MSME tax rights and obligations. The community service activities still need follow-up activities to ensure that the MSME actors have correctly calculated their tax obligations and have fulfilled their tax obligations by the applicable regulations. Therefore, the community service activities can be continued in the following year's activities.